Pengembangan Media Pembelajaran PAI Berbasis IT - Agus Hariyanto; Faridi Faridi (Jurnal Budi Pekerti Agama Islam, 2024)
This article aims to enable learning to be more advanced and developed so that learning becomes more effective and efficient. In addition, Islamic religious education aims to develop attitudes and characters that are loyal and devoted to Allah SWT and in line with current realities. All educational institutions must be proactive, creative and productive in reading the phenomena that occur today. Therefore, the role of IT is very important here, creating a good design as a foundation for the advancement of information and communication technology, and adding Islamic religious education learning activities with materials and skills and practicing religion includes learning activities and mastery. But we must also be able to use a technical approach with learning methods using the internet programme "Moodle". Furthermore, the researcher will provide information regarding the type of research to be conducted, the time plan for conducting the research, and the class that will be the subject of the research. The results achieved are the process of developing IT-based PAI learning media, starting from the initial identification stage or the implementation of preliminary research to the final revision stage.